Assessment of Extrusion and Postoperative Pain of a Bioceramic and Resin-Based Root Canal Sealer - Fonseca, Braúlio; Coelho, Marcelo Santos; Bueno, Carlos Eduardo da Silveira; Fontana, Carlos Eduardo; Martin, Alexandre Sigrist De; Rocha, Daniel Guimarães Pedro (European Journal of Dentistry, 2019)
Objectives The objective of this study was to compare a bioceramic and a resin-based endodontic sealer with regard to extrusion and postoperative pain.Materials and Methods Sixty-four patients requiring endodontic treatment of single-rooted maxillary teeth with necrotic pulps were included in this study. The root canal treatments were performed in a single visit using a size 40.06 single-file reciprocating system under 2.5% NaOCl irrigation. After irrigation with 17% ethylenediaminetetraacetic acid (EDTA) and 2.5% NaOCl, the canals were dried and randomly divided into two different groups (n = 32) depending on the sealer used: resin-based group (RG) in which the canals were filled with the AH Plus, and the bioceramic group (BG) in which the canals were filled with the Sealer Plus BC. Ibuprofen (600 mg) was prescribed every 6 hours if the volunteers experienced pain. The patients registered their pain sensation in a visual analog scale (VAS) card, ranging from 0 to 10 at 24-hour, 48-hour, 72-hour, and 1-week intervals. Statistical analysis  For statistical analysis, the level of significance was set at p < 0.05.Results Sealer extrusion occurred in nine patients of the RG and in 19 patients of the BG (p < 0.05). The average pain level at 24-hour and 48-hour intervals was, respectively, 1.46 ± 1.96 and 0.44 ± 0.86 for RG, and 1.21 ± 2.09 and 0.09 ± 0.38 for BG. There was no report of pain after 48 hours. The mean number of tablets taken for pain relief was 0.03 ± 0.17 for RG and 0.06 ± 0.24 for BG. No statistically significant difference was found with regard to pain level and intake of pain killer tablets (p > 0.05).Conclusions The BG sealer presented significantly more extrusion than the RG sealer. Sealer extrusion was not associated with pain. The average pain level and the mean number of tablets taken for pain relief were similar in both groups.
Keywords: root canal treatment; bioceramic; pain; reciprocating; resin-based sealer